(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Technical communication plays a pivotal role in an organization, whether it is a business enterprise, an industry, or an academic institution. All managerial or administrative activities involve communication, be it planning, organizing, recruiting, coordinating, or decision- making. When you write reports, give instructions, or read brochures and manuals, you are involved in the process of communication. Communication serves as an instrument to measure the success or growth of an organization. The success of any organization is largely recognized by the quality and quantity of information flowing through its personnel. The various types of communication not only help an organization to grow, but also enable the communicators to develop certain attributes.